Association of placental fatty acid desaturase 2 (FADS2) methylation with maternal fatty acid levels in women with preeclampsia. (September 2022) - Dave, Kinjal; Kaur, Lovejeet; Sundrani, Deepali; Sharma, Preeti; Bayyana, Swati; Mehendale, Savita; Randhir, Karuna; Chandak, Giriraj R; Joshi, Sadhana
Highlights: Altered DNA methylation in FADS2 gene in the placentae of women with preeclampsia. Altered levels of maternal plasma fatty acids in women with preeclampsia. Association of DNA methylation changes with maternal plasma fatty acids. Association of DNA methylation changes with ∆−6 desaturase enzyme index. Abstract: Introduction: Biosynthesis of long-chain polyunsaturated fatty acids requires sequential activities of desaturases and elongases for conversion of fatty acid precursors to products. The delta-6 desaturase enzyme, encoded by FADS2 gene, is a rate limiting enzyme in this pathway. Alterations in D6D enzyme activity can lead to altered fatty acid profiles. Objectives: To examine differences in placental DNA methylation (DNAm) and expression of FADS2 gene in preeclampsia women compared to normal women and their association with maternal variables (plasma fatty acids, desaturase enzyme index, blood pressure), placental weight and birth outcomes. Methods: DNAm and expression of FADS2 gene were examined in placentae of normotensive ( n  = 100) control and preeclampsia ( n  = 100) women using pyrosequencing and quantitative real-time PCR respectively. Women with preeclampsia included those delivering at term ( n  = 43, gestation ≥ 37 weeks; T-PE) or preterm ( n  = 57, gestation < 37 weeks; PT-PE). A total of 26 CpGs in FADS2 promoter and region around it, were analysed in two PCR reactions (region 1 and 2). Results: Out of 13 CpGs in region 1, significant hypermethylation was noted at CpG3 in T-PE ( p  = 0.03) and of 13 CpGs in region 2, CpG2 ( p  = 0.008), CpG11 ( p  = 0.04), CpG12 ( p  = 0.001) were hypomethylated and CpG13 ( p  = 0.001) was hypermethylated in preeclampsia group, as compared to controls. FADS2 expression was lower in PT-PE as compared to controls ( p  = 0.04). DNAm at various CpGs in the FADS2 were associated with maternal plasma FADS2 enzyme index and also associated with maternal fatty acid levels. However, we did not observe any association of DNAm with maternal blood pressure, placental weight and birth outcomes. Conclusions: This study for the first time reports differential methylation of FADS2 and its association with impaired maternal fatty acid metabolism in preeclampsia and provides a mechanistic basis to our earlier observations of altered maternal LCPUFA levels in women with preeclampsia.